2022
DOI: 10.1002/cam4.4822
|View full text |Cite
|
Sign up to set email alerts
|

TGIF1 overexpression promotes glioma progression and worsens patient prognosis

Abstract: Transforming growth factor β‐induced factor homeobox 1 (TGIF1) reportedly promotes the pathological processes of various malignant tumors. However, few studies have investigated the role of TGIF1 in gliomas. We aimed to explore the relationship between TGIF1 expression and the clinical characteristics of patients with glioma, including their overall survival. A total of thousands transcriptome datapoints were downloaded from public databases to determine the correlations between TGIF1 and various clinicopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 47 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Moreover, we recently demonstrated that inhibition of COL1A1 expression within the tumor cells reprogramed the tumoral microenvironment and inhibited tumor invasion and progression ( 15 ). Upregulation of certain growth factor such as TGF-β, can also contribute to ECM upregulation in gliomas ( 178 ).…”
Section: Non-cellular Components Of the Microenvironmental Landscape ...mentioning
confidence: 99%
“…Moreover, we recently demonstrated that inhibition of COL1A1 expression within the tumor cells reprogramed the tumoral microenvironment and inhibited tumor invasion and progression ( 15 ). Upregulation of certain growth factor such as TGF-β, can also contribute to ECM upregulation in gliomas ( 178 ).…”
Section: Non-cellular Components Of the Microenvironmental Landscape ...mentioning
confidence: 99%